Labour Market Challenges in Light of Changes Caused by Technological Development: A Student Perspective - Magdalena GORZELANY – DZIADKOWIEC; Małgorzata KOSAŁA (Communications of International Proceedings, 2021)
Implementing digital technologies in the industry and institutions, which need to keep up with changes, builds up new expectations for employee qualifications. Undoubtedly, ‘new technologies will radically change the nature of work in all industries and professions. The primary uncertainty stems from the questions: to what degree automation will replace the workforce, how long it will take, and how far it will go’. Hence, the objective of the paper was to analyse changes in the employment structure and competencies in demand for Industry 4.0 and 5.0. A hypothesis is put forward to pursue the objective that technology changes brought by Industry 4.0 and 5.0 will cause new professions to emerge. The objective and research questions of the paper were pursued with a traditional literature review. Reports and statistical data were analysed to identify changes in the labour market and competencies in demand for Industry 4.0 and 5.0. Furthermore, the author conducted an original diagnostic survey using an original questionnaire with a respondent data section and close-ended questions.  Responses were collected using the CAWI technique. The analyses yielded a conclusion that technology changes brought by Industry 4.0 and 5.0 will cause new professions to emerge. The results suggest that the most demanded professions are application developer, software analyst, information security analyst, and financial analyst. According to the respondents, managing directors and marketing and sales specialists would be appreciated as well. The most demanded employee competencies in the next decade will be analytical and innovative thinking, creativity, initiative, flexibility emotional intelligence.
Keywords: Labor market; technological progress; employee competences 4.0; revolution 5.0